Best choice for a beef cut: Choice - Pappas, Mike (Raton, NM Raton Range, 1989)
Columns written by Mike Pappas, owner of the Sweet Shop Restaurant, for the Raton Daily Range on a wide variety of topics, some historical, some current, some personal.
Newspaper Article by Mike Pappas
Master list item #: 73
File location is in the Raton File Cabinet
Keywords: Agricultural Marketing Service; United Sttes Department of Agriculture; U.S. Department of Commerce's National Marine Fisheries Service; National Restaurant Association; Life and Customs; Local History; Grading Food; Quality of food; Meat Standards; Beef Cut; Prime Cut; Choice Cut; Select; Standard Cut; Commercial; Cutter and Canner